Niche WNT5A regulates the actin cytoskeleton during regeneration of hematopoietic stem cells - Schreck, Christina; Istvanffy, Rouzanna; Ziegenhain, Christoph; Sippenauer, Theresa; Ruf, Franziska; Henkel, Lynette; Gaertner, Florian; Vieth, Beate; Florian, M. Carolina; Mende, Nicole; Taubenberger, Anna; Prendergast, Aine; et al. (Journal of Experimental Medicine, 2017)
Here, we show that the Wnt5a-haploinsufficient niche regenerates dysfunctional HSCs, which do not successfully engraft in secondary recipients. RNA sequencing of the regenerated donor Lin- SCA-1+ KIT+ (LSK) cells shows dysregulated expression of ZEB1-associated genes involved in the small GTPase-dependent actin polymerization pathway. Misexpression of DOCK2, WAVE2, and activation of CDC42 results in apolar F-actin localization, leading to defects in adhesion, migration and homing of HSCs regenerated in a Wnt5a-haploinsufficient microenvironment. Moreover, these cells show increased differentiation in vitro, with rapid loss of HSC-enriched LSK cells. Our study further shows that the Wnt5a-haploinsufficient environment similarly affects BCR-ABLp185 leukemia-initiating cells, which fail to generate leukemia in 42% of the studied recipients, or to transfer leukemia to secondary hosts. Thus, we show that WNT5A in the bone marrow niche is required to regenerate HSCs and leukemic cells with functional ability to rearrange the actin cytoskeleton and engraft successfully.
CRIS-Team Scopus Importer:2022-08-05